The importance of higher education and influences as good management of Colombia rulers (2016)
Currently there is evidence that good governance managers is not results oriented social welfare, constantly identifies the sake affecting society seeks, therefore it is important to note that many of the officials not They found in the ability to cope with the responsibility of managing the resources of a society because they lack knowledge and fundamental to good management values for that reason the importance of higher education is related and how it affects the management of rulers to who every day strengthen democratic leadership, the functions to be carried out in an excellent strategic planning aimed at strengthening governance results.